2011
DOI: 10.1186/1471-2350-12-95
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of innate immunity-related inflammatory pathways and their association with factors related to type 2 diabetes

Abstract: BackgroundType 2 diabetes mellitus (T2DM) has been linked to a state of pre-clinical chronic inflammation resulting from abnormalities in the innate immune pathway. Serum levels of pro-inflammatory cytokines and acute-phase proteins, collectively known as 'inflammatory network', are elevated in the pre-, or early, stages of T2DM and increase with disease progression. Genetic variation can affect the innate immune response to certain environmental factors, and may, therefore, determine an individual's lifetime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 66 publications
1
51
1
Order By: Relevance
“…Genetic factors play key roles in the pathogenesis of T2DM. TLR4 is one of the most important candidate genes for T2DM, and genetic variants in the TLR4 gene have been reported to be associated with T2DM susceptibility (Illig et al, 2003;Rudofsky et al, 2004;Creely et al, 2007;Kim et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013). In this study, we demonstrated an association between the g.12375A>G and g.14367G>A genetic variants of the TLR4 gene and the risk of T2DM in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Genetic factors play key roles in the pathogenesis of T2DM. TLR4 is one of the most important candidate genes for T2DM, and genetic variants in the TLR4 gene have been reported to be associated with T2DM susceptibility (Illig et al, 2003;Rudofsky et al, 2004;Creely et al, 2007;Kim et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013). In this study, we demonstrated an association between the g.12375A>G and g.14367G>A genetic variants of the TLR4 gene and the risk of T2DM in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 49%
“…To date, several single nucleotide polymorphisms (SNPs) have been identified in the human TLR4 gene (Raby et al, 2002;Kolz et al, 2008;Arora et al, 2011;Jiang et al, 2013), such as Asp299Gly (Rudofsky et al, 2004;Kim et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013) and Thr399Ile (Rudofsky et al, 2004;Kim et al, 2008;Kolz et al, 2008;Buraczynska et al, 2009;Maldonado-Bernal et al, 2011;Jiang et al, 2013). Furthermore, several studies proved that the TLR4 gene variants were associated with susceptibility to T2DM (Rudofsky et al, 2004;Kim et al, 2008;Kolz et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013). However, the data from these studies are inconsistent, and the exact mechanism is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular methylation processes are ubiquitous metabolic events (29 -32) that are linked to redox status (33) and involved in immune processes (34), both processes known to be involved in obesity and the progression of type II diabetes (35,36). SAM and SAH levels as well as protein-arginine methylation are altered in diabetic models (5-9) and in humans (10, 11).…”
Section: Discussionmentioning
confidence: 99%